Line and the Circle: the Family and the ‘Dialectics in Institutions’ between Subversion and Resistance - Okić, Tijana (B@belonline, 2022)
Hegel is the philosopher of the circle. He famously posits the circular logic against virtually the entirety of modern philosophy, which equates the circle with tautology, petitio principii and ultimately falsehood. In line with such a view, this paper poses the question: what is the relationship between the linear logic and Hegel’s circular logic when it comes to the family as an institution within the sphere of objective spirit? For Hegel, institutions, in order to be worthy of such a name (or concept), imply a circular, rather than merely linear logic. Institutions, however, may be created by linear logic of subversion and irruption in history, but whether they persist or not is entirely a question of resistance and thus circularity, that is, their own repetition and reproduction in and through time and history. Following on from this, the paper argues that the peculiar position of the family within Hegel’s system of institutions stems from what here is termed the «two bodies of the family». The two bodies of the family enable us to understand the contradictory position that the family occupies and is assigned to this day, placing it in a permanent dialectical tension between the line and circle, resistance and subversion.